2010
DOI: 10.1021/ol1012372
|View full text |Cite
|
Sign up to set email alerts
|

Branch-Selective Synthesis of Oxindole and Indene Scaffolds: Transition Metal-Controlled Intramolecular Aryl Amidation Leading to C3 Reverse-Prenylated Oxindoles

Abstract: In an effort to access biologically important scaffolds, a concise branch-selective synthesis of C3 tertiary oxindoles by Cu(I)-catalyzed aryl amidation and 2,2-dimethyl indene by Pd(0)-catalyzed Heck cyclization has been accomplished from acyclic reverse-prenylated intermediates. Oxindole C3-enolate generation using NaH followed by alkylation in the presence of appropriate electrophiles provides a novel route to quaternary C3 reverse-prenylated oxindoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The amides are generated in short time scales, in high yield and with no complex post VFD operations required, with the product simply collected, washed with 2 M HCl, dried and recrystallized if obtained as a solid. In furthering this flow methodology, other factors were subsequently explored, namely, the use of an inert atmosphere of argon blanket over the film to circumvent mass transfer of moisture from air into the thin film, which could hydrolyze the acyl chloride, and the use of pyridine as the base, which is common in acylation reactions 23. 24 However, the effect on the yield was minimal (see the Supporting Information).…”
Section: Yields Of Amides Formed In the Vfd Under Flow With The Optimmentioning
confidence: 99%
See 1 more Smart Citation
“…The amides are generated in short time scales, in high yield and with no complex post VFD operations required, with the product simply collected, washed with 2 M HCl, dried and recrystallized if obtained as a solid. In furthering this flow methodology, other factors were subsequently explored, namely, the use of an inert atmosphere of argon blanket over the film to circumvent mass transfer of moisture from air into the thin film, which could hydrolyze the acyl chloride, and the use of pyridine as the base, which is common in acylation reactions 23. 24 However, the effect on the yield was minimal (see the Supporting Information).…”
Section: Yields Of Amides Formed In the Vfd Under Flow With The Optimmentioning
confidence: 99%
“…In furthering this flow methodology, other factorsw ere subsequently explored, namely,t he use of an inert atmosphere of argon blanket over the film to circumvent mass transfer of moisture from air into the thin film, which could hydrolyzet he acyl chloride, and the use of pyridine as the base, which is common in acylation reactions. [23,24] However, the effect on the yield was minimal (see the Supporting Information). Some subtle features related to flow rate were also revealed in this exploratory work.…”
mentioning
confidence: 99%
“…Starting from 1a and 1a-alike cMAVIs, our structurally diversified coupling products 4 could be transformed into different series of heterocyclic fragments ( Figure 4 ). 4aa-4ag underwent palladium-catalyzed intracellular C-N formation to accomplish the indole ring construction in series 1 compounds (5a-5g) ( Bugaenko et al., 2018 ; Ignatenko et al., 2010 ). Meanwhile, the terminal vinyl double bond in 4aa could be used as an acceptor for halogenation ( Meimetis et al., 2014 ; Song et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have established aP d-catalyzedintramolecularamidation of aryl bromides using palladium acetate-BINAP [5] as the catalyst furnishing the novel conjugates of N-phenylbenzofuran-2-carboxamides with a2 -oxindole [6] linked through aC-N single bond. The crystal structure analysis of the title compound revealed that geometric parameters of the title compound are in the normalranges.…”
Section: Discussionmentioning
confidence: 99%